Sustainable pork production and processing: a step toward empowering tribal women in Northeast India - Mehta, Shivani; Bhattacharjee, Mahua (Frontiers in Nutrition, 2024)
This study explores the transformative potential of sustainable pork production and processing as a tool to empower tribal women in the Northeast Region (NER) of India. NER is faced with multiple challenges like poverty, gender inequality, and poor livelihood methods. Therefore enhancing sustainable production and processing methods for pork (it being their staple food), presents not only an opportunity for socio-economic development of the region but also an effective tool for economic empowerment of tribal women. Through a primary survey of pork value chain actors in Assam, Meghalaya, and Nagaland (the largest producers and consumers of pork in NER) the study outlines the current practices and barriers in sustainable pork production methods. The study reveals that even though the consumption of pork has remained unchanged and that of processed pork items is on a rise, the production of pork is drastically declining. Therefore reviving the pork production in NER can be instrumental in building sustainable livelihood models especially for tribal women in the region. The study explores the effectiveness of a community-based, 'model village approach' where capacity building around sustainable pork production, processing and waste management techniques results in economic empowerment of women. Findings from the post-impact analysis of the capacity building approach calls for policy intervention and the establishment of supportive networks to enhance the growth of sustainable pork production system in NER, thereby contributing to the attainment of SDG targets proposed by the Indian economy.